Reticulon Homology Domain-Containing Proteins and ER-Phagy - D’Eletto, Manuela; Oliverio, Serafina; Di Sano, Federica (Frontiers in Cell and Developmental Biology, 2020)
The endoplasmic reticulum is a dynamic membrane system comprising different and interconnected subdomains. ER structure changes in response to different stress conditions through the activation of a selective autophagic pathway called ER-phagy. This represents a quality control mechanism for the ER turnover and component recycling. Several ER-resident proteins have been indicated as receptors for ER-phagy; among these there are proteins characterized by the presence of a reticulon homology domain (RHD). RHD-containing proteins promote ER fragmentation by a mechanism that involves LC3 binding and lysosome delivery. Moreover the presence of a correct RHD structure is closely related to their capability to regulate ER-shape and morphology by curvature induction and membrane remodelling. Deregulation of ER-selective autophagic pathway due to defects in proteins with RHD have been implicated in several human diseases in particular infectious and neurodegenerative diseases as well as in cancer development. While the molecular mechanisms and the physiological role of ER-phagy are not yet fully understood, it is quite clear that this process is involved in different cellular signalling pathways and has an impact in several human pathologies.